On solving selected problems of linear algebra by means of neural networks = Zagadnienie rozwiązywania wybranych zadań algebry liniowej za pomocą sieci neuronowych - Mrówczyńska, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents selected practical applications and results of computer simulations from the field of numerical linear algebra realized by means of neural networks. Bearing in mind aspects of applications, it has been decided that priority should be given to the description of the problem of soling over-determined linear systems in the norm l_2 and the norm l_1.
Keywords: sieci neuronowe; algebra liniowa; neural networks; linear algebra; linear systems